Heterogeneous aggregation of microplastics and mineral particles in aquatic environments: Effects of surface functional groups, pH, and electrolytes - Yanhua Wang; Zhengli Tang; Yingnan Liu; Yilin Qian; Shuo Yang; Anqi Wang; Zhibao Dong; Baoshan Xing (Environmental Chemistry and Ecotoxicology)
Microplastics (MPs) aggregation critically governs their environmental transport, yet interactions with mineral surfaces remain underexplored. In this study, polyethylene (PE) MPs were employed as model particles to prepare both pristine PE and bovine serum albumin (BSA)-coated PE (B-PE). The heterogeneous aggregation of these particles with inorganic minerals (goethite, hematite, pyrite, magnetite) and clay minerals (kaolinite, montmorillonite) was systematically investigated under varying pH conditions (3.0, 6.0, 9.0) and ionic strengths (NaCl 5–300 mmol/L, CaCl2 1–50 mmol/L). Results demonstrated that positively charged inorganic minerals exhibited significantly stronger heterogeneous aggregation with negatively charged PE, exhibiting aggregation capacities 2.97 times higher than those of negatively charged clay minerals. The introduction of oxygen-containing functional groups such as COOH and OH on the B-PE surface not only enhanced electrostatic attraction but also facilitated ligand exchange and hydrogen bonding, further improving aggregation efficiency. At pH 3.0, removal efficiencies of PE and B-PE for inorganic minerals exceeded 90 %, while aggregation was nearly completely inhibited at pH 9.0. With increasing NaCl concentration, the critical coagulation concentration (CCC) of B-PE decreased by 29.6 %–42.6 % compared to pristine PE. Moreover, Ca2+ ions exhibited a stronger promoting effect on aggregation via cation bridging than Na+ ions. These findings reveal the synergistic regulatory effects of mineral type, protein coating, and environmental factors on microplastic-mineral heterogeneous aggregation, providing a theoretical foundation for predicting the transport and fate of microplastics in complex natural aquatic environments, as well as for developing biomolecule-based sustainable remediation strategies.